Sosialisasi Penggunaan Aplikasi Dropbox Business Untuk Menangani Kendala Pada Koperasi Simpan Pinjam Balo’Toraja - Masdar Ryketeng; Nur Luthfiah. Z; Nurdifna Az-Zahra; Warka Syachbrani; Irwandi (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
The problem specifically faced by KSP Balo'Ta is that members sometimes do not complete the specified requirements because members forget to bring the necessary documents or files. The aim of this research is to find out the problems or obstacles that exist in the Savings and Loans Cooperative, KSP Balo'Ta can utilize the Dropbox Business application as a solution to the problems faced and KSP can improve the quality of its cooperative. In this research method which involves collecting data from respondents through questionnaires or interviews. The respondent in this research is Mrs. Yuyun Meidita as the Manager at KSP Balo'Ta. From this research, a solution has been obtained, namely that KSP Balo'Ta can use the Dropbox Business application as a document storage facility.